2004
DOI: 10.1111/j.1365-2699.2004.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical analysis of species of the tribe Cytiseae (Fabaceae) in the Iberian Peninsula and Balearic Islands

Abstract: Aim To analyse quantitatively the biogeographical distribution pattern of species of the Cytiseae Bercht. & J. Presl (¼ Genisteae Benth.) tribe in the Iberian Peninsula and the Balearic Islands, and to identify environmental variables related to the distributional patterns.Location Iberian Peninsula and Balearic Islands, using the 61 administrative provinces as operational geographical units.Methods In order to identify chorotypes (groups of species with similar geographical distribution), we performed a upgma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Although some authors have suggested that basic patterns have emerged in Iberian biotic regionalization (Real et al 1996;Gómez-González et al 2004;Arroyo et al 2004), divergence among published proposals still emerges (i.e. Vargas et al 1998;Rivas Martínez and Loidi 2000;García Barros et al 2002).…”
Section: Iberian-balearic Fern Regionsmentioning
confidence: 95%
“…Although some authors have suggested that basic patterns have emerged in Iberian biotic regionalization (Real et al 1996;Gómez-González et al 2004;Arroyo et al 2004), divergence among published proposals still emerges (i.e. Vargas et al 1998;Rivas Martínez and Loidi 2000;García Barros et al 2002).…”
Section: Iberian-balearic Fern Regionsmentioning
confidence: 95%
“…This is evident in the relation between D. lanosa and D. wrightii; these 2 taxa are morphologically similar (Luna et al, 2000), genetically related (Palomino et al, 1988;Jiao et al, 2002) and both are distributed in arid northwestern Mexico, even though D. wrightii is more common in the southwestern United States. On the other hand, comparable distribution patterns of taxonomically unrelated species may indicate the occupation of microhabitats within a broad ecological region suggesting their tolerance of certain climatic parameters that results in sympatry of species from different sections (Gómez-González et al, 2004); such as the case of D. inoxia, D. quercifolia, and D. ceratocaula, of sections Dutra, Datura, and Ceratocaulis, respectively (Satina and Avery, 1959;Hammer et al, 1983) that grow together on the Mexican Plateau.…”
Section: Intraset Correlations T-valuesmentioning
confidence: 99%
“…Endemic species are the result of isolation due to geographical and ecological barriers (Gómez-González et al, 2004); this explanation is appropriate in the case of D. kymatocarpa, a species endemic to the DB province in Guerrero, an inland basin surrounded by the EV and SMS, a site where numerous endemic species from different taxonomic groups have been recorded (Kohlmann and Sánchez, 1984). Also, many endemic taxa in Mexico are concentrated mainly in regions with dry climatic conditions (Rzedowski, 1993); in the case of Datura, this applies to D. lanosa and D. reburra, native to the dry northwestern areas of Mexico.…”
Section: Intraset Correlations T-valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Less often chorological differentiation of woody flora is taken into consideration (Ojeda & al. 1998;Gómez-González & al. 2004;Kosiński 2005;Abbate & al.…”
Section: Introductionmentioning
confidence: 99%